O acento primário em português brasileiro: uma abordagem não-métrica. - Alves, Gilson Chicon (2012)
The phenomenon that we propose to analyze in this work is the accent of the Brazilian Portuguese (based on PB), according to Câmara Júnior (1970, p. 63), it is characterized as a greater inspiration power, or the emission intensity, of the vowel of a syllable in contrast with other vowels . The general objective of this work is to discuss the criteria which define the Brazilian Portuguese accent pattern. In order to achieve that goal, a work was carried out based on data previously taken in several studies there are in Brazil. We understand that it is not necessary to take more data, as long as there are variation studies with true results which are worth to support our thesis and according to it, the primary accent of the Brazilian Portuguese is free, variable (on the edges), unpredictable, therefore, it can not be predicted by any rule or restriction unless stipulations are considered, what ends up bringing much stress to the Metrical phonology. We decline the Metrical Phonology as it is constituted nowadays for that theory consider the primary accent as secondary and the secondary as primary, what brings inaccurate results, not trustable enough because the criteria used in that theory sensitivity meaningful to a sort of support what characterizes the Brazilian Portuguese accent seem not to be appropriate to an analysis of that system. We postulate that the primary accent is considered as primary, as states the First Primary Accent Theory PAF proposed by van der Hulst (1997, 2006), that is the guiding of this work. According to the PAF, there are two necessary criteria for placing the primary accent: the special syllable and the dominium. Based on that theory the special syllable is the one which gets a lexical mark motivated for getting that feature. Concerning the dominium, this involves the two last syllables (right to left), being, in this case, an optional extra metrical fact. In that point, we disagree with the approach proposed by van de Hulst for we postulate the enlargement from two to three syllables next to the right end the group of three syllables is perfectly predictable by the Metrical Phonology, with a difference from that theory, so that the third part of that group is closed.